Upaya Peningkatan Produktivitas Lini Produksi PT X dengan Metode Value Stream Mapping - Garry Rezky Putra Tantowi; Benedictus Rahardjo (Jurnal Titra, 2020)
PT X is a company that produces cigarette filters. They try to continuously improve. One of them is by increasing productivity on the production line. Productivity at PT X is affected by several factors. Two of them are Availability Rate (AR) and Performance Rate (PR). Based on the data collected in January 2020, the rate of AR is 85% and PR is 88%, with a productivity rate of 656.8 tray filters per operator. The company has set the minimum rate for AR and PR are 90% dan 95% for each. Therefore, improvements are needed. One of the tools that can be used to increase productivity is value stream mapping to build the current state map. To increase the rate, some improvement that can be done is by making Standard Operating Procedure (SOP) on cleaning processes of the machine and the area around. In addition, check the lifetime of the grinding blade before starting the production and apply line balancing to the process in order to prevent bottleneck. Then, build the future state map. Thus, each of the AR and PR rates are expected to increase to 90% and 95% so that in the end it can increase the productivity.